Comparison of Effects of an Endotracheal Tube or Facemask on Breathing Pattern and Distribution of Ventilation in Anesthetized Horses - Moreno-Martinez, Fernando; Byrne, David; Raisis, Anthea; Waldmann, Andreas D.; Hosgood, Giselle; Mosing, Martina (Frontiers in Veterinary Science, 2022)
Equine respiratory physiology might be influenced by the presence of an endotracheal tube (ETT). This experimental, randomised cross-over study aimed to compare breathing pattern (BrP) and ventilation distribution in anaesthetised horses spontaneously breathing room air via ETT or facemask (MASK). Six healthy adult horses were anaesthetised with total intravenous anaesthesia (TIVA; xylazine, ketamine, guaiphenesin), breathing spontaneously in right lateral recumbency and randomly assigned to ETT or MASK for 30 minutes, followed by the other treatment for an additional 30 minutes. During a second anaesthesia one month later, treatment order was inversed. Electrical impedance tomography (EIT) using a thoracic electrode belt, spirometry, volumetric capnography, oesophageal pressure difference (ΔPoes), venous admixture, and laryngoscopy data were recorded over 2 minutes every 15 minutes. Breaths were classified as normal or abnormal according to the EIT impedance curve. A mixed linear model was used to test the effect of treatment on continuous outcomes. Cochran-Mantel-Haenszel analysis was used to test for associations between global BrP and treatment. Global BrP was associated with treatment (p=0.012) with more abnormal breaths during ETT. CoVRL showed more ventilation in the non-dependent lung during ETT (p=0.025). I:E ratio was shorter (p=0.017), peak expiratory flow (p=0.009) and physiologic dead space (p=0.034) were larger and ΔPoes (p<0.001) was smaller with ETT. The presence of an ETT alters BrP and shifts ventilation towards the non-dependent lung in spontaneously breathing horses anaesthetised with TIVA.